The Associations of Parental Harsh Discipline, Adolescents’ Gender, and Grit Profiles With Aggressive Behavior Among Chinese Early Adolescents - Cui, Guanyu; Lan, Xiaoyu (Frontiers in Psychology, 2020)
Although the association between parental harsh discipline and aggressive behavior in adolescence has been well established, little attention has been paid to early adolescence. Moreover, the risk and protective factors (the interplay of parents’ and adolescents’ gender, the role of grit) in this association during this period are still less explored in the literature. Guided by a socioecological framework, the current study (more exploratory in nature) identified the grit profiles based on two dimensions (i.e., perseverance and consistency) in a sample of Chinese early adolescents; likewise, this study further investigated gender specific patterns and the moderating role of grit profiles in the association between parental harsh discipline and aggressive behavior. A total of 1,156 Chinese early adolescents (46.5% girls) were involved in this study and completed a set of self-report questionnaires. Latent profile analysis revealed three profiles of grit: low perseverance and low consistency, high perseverance and low consistency, and high perseverance and high consistency. Moreover, linear regression analysis indicated that paternal and maternal harsh discipline were each positively associated with aggressive behavior. The positive association between paternal harsh discipline and aggressive behavior was only significant for adolescent boys with low levels of perseverance and consistency; in contrast, the positive association between maternal harsh discipline and aggressive behavior was significantly stronger for adolescent boys with high levels of perseverance and consistency. These findings suggest that parental harsh discipline presents a risk factor for aggressive behavior, especially for adolescent boys in early adolescence; such a vulnerable effect is more heightened for those with low levels of perseverance and consistency. In addition, although grit is assumed to be a positive personal attribute, maternal harsh discipline to boys in the Chinese family context may disturb their positive development pathway during early adolescence, which is highly discouraged.